2018
DOI: 10.1037/ccp0000317
|View full text |Cite
|
Sign up to set email alerts
|

More than my RA: A randomized trial investigating body image improvement among women with rheumatoid arthritis using a functionality-focused intervention program.

Abstract: Focusing on body functionality can improve body image and reduce depression in women with rheumatoid arthritis. The intervention technique is easy and affordable to deliver and could be a fruitful addition to extant treatments for rheumatoid arthritis. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 32 publications
4
44
0
Order By: Relevance
“…Interestingly, some parents discussed the need to develop their child’s self-esteem in other areas than appearance as a mechanism for protecting them against the impact of having a condition that affects appearance. Recent studies suggest that interventions focussed on developing focus on body functionality can have positive effects in reducing distress associated with visible difference (Alleva et al, 2018). Children in the current study also reported that friends played an important role in helping them to feel accepted and this fits with studies with other populations (Feragen et al, 2010) and suggests that there are significant benefits to be gained when services can foster peer support.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some parents discussed the need to develop their child’s self-esteem in other areas than appearance as a mechanism for protecting them against the impact of having a condition that affects appearance. Recent studies suggest that interventions focussed on developing focus on body functionality can have positive effects in reducing distress associated with visible difference (Alleva et al, 2018). Children in the current study also reported that friends played an important role in helping them to feel accepted and this fits with studies with other populations (Feragen et al, 2010) and suggests that there are significant benefits to be gained when services can foster peer support.…”
Section: Discussionmentioning
confidence: 99%
“…The studies took place in six countries: seven in the USA (Albertson et al, 2015;Annesi, 2005;Bush, Rossy, Mintz, & Schopp, 2014;Pinto, Clark, Maruyama, & Feder, 2003;Rodgers et al, 2018;Toole & Craighead, 2016;Wolfe & Patterson, 2017), three in the UK (Alleva, Diedrichs, Halliwell, Martijn, et al, 2018;Alleva, Diedrichs, Halliwell, Peters, et al, 2018;Jankowski et al, 2017), two in Portugal (Duarte, Pinto-Gouveia, & Stubbs, 2017;Pinto-Gouveia et al, 2017), and one study in Australia (Mellor, Connaughton, McCabe, & Tatangelo, 2017), Iran (Ahmadi, Abbaspoor, Behroozy, & Malehi, 2017), and the Netherlands (Alleva, Martijn, et al, 2015). There was significant variation in sample size between the studies, ranging from 20 to 274 participants (M = 105.7).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Thus, most of the sample were classified as adults. Nonetheless, most studies (n = 12) used women-only samples (Ahmadi et al, 2017;Albertson et al, 2015;Alleva, Diedrichs, Halliwell, Martijn, et al, 2018;Alleva, Diedrichs, Halliwell, Peters, et al, 2018;Alleva, Martijn, et al, 2015;Annesi, 2005;Bush et al, 2014;Duarte et al, 2017;Pinto-Gouveia et al, 2017;Pinto et al, 2003;Toole & Craighead, 2016;Wolfe & Patterson, 2017).…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, patients with RA, especially those with aggressive disease, often experience changes in their physical appearance and function [58]. For example, women with higher degree of morning stiffness have been shown to be more concerned over their body image and have reported more sexual dissatisfaction [59].…”
Section: The Psychosocial Impact Of Non-inflammatory Pain In Women Wimentioning
confidence: 99%